2014
DOI: 10.1021/op400302b
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Catalysis with Disaccharide Phosphorylases: Chemoenzymatic Synthesis of α-d-Glucosides Using Sucrose Phosphorylase

Abstract: Thanks to its broad acceptor specificity, sucrose phosphorylase (SP) has been exploited for the transfer of glucose to a wide variety of acceptor molecules. Unfortunately, the low affinity (K m > 1 M) of SP towards these acceptors typically urges the addition of cosolvents, which often either fail to dissolve sufficient substrate or progressively give rise to enzyme inhibition and denaturation. In this work, a buffer/ethyl acetate ratio of 5:3 was identified to be the optimal solvent system, allowing the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Interestingly,t he activity of bothi CLEAs towards glucose was decreased by 80 and 45%, respectively,i ndicating altered specificity rather than stabilization.I n contrastt oS P, [13] imprintingw ith the acceptor molecule rather than the glucoside was found to enhance the desired glycosylation activity.A lthough concentrationsu pt o2 0gL À 1 octyl b-d-glucopyranoside were readily achieved (donor yield:5 5%), higher conversions could not be reached due to hydrolysis of aG1P. Such al imitationh as also been reported for sucrose phosphorylase, [11] but could potentially be alleviated by enzyme engineering.…”
Section: Imprinted Cross-linked Enzyme Aggregates (Icleas) Of Cpmentioning
confidence: 86%
See 2 more Smart Citations
“…Interestingly,t he activity of bothi CLEAs towards glucose was decreased by 80 and 45%, respectively,i ndicating altered specificity rather than stabilization.I n contrastt oS P, [13] imprintingw ith the acceptor molecule rather than the glucoside was found to enhance the desired glycosylation activity.A lthough concentrationsu pt o2 0gL À 1 octyl b-d-glucopyranoside were readily achieved (donor yield:5 5%), higher conversions could not be reached due to hydrolysis of aG1P. Such al imitationh as also been reported for sucrose phosphorylase, [11] but could potentially be alleviated by enzyme engineering.…”
Section: Imprinted Cross-linked Enzyme Aggregates (Icleas) Of Cpmentioning
confidence: 86%
“…Separation was performed on Merck Silica gel 60 F 254 precoated plates.T he eluent was am ixture of EtOAc:MeOH:-water (30:5:4), and spots were visualized by UV detection at 254 nm, or charring with 10% (v/v) H 2 SO 4 .T he concentration of glucosides was determined by HPLC analysis.A dequate separationa nd detection was achieved using an Xbridge amide column (250 mm 4.6 mm, 3.5 mm, Waters, USA) coupled with an Alltech 2000ES evaporative light scattering detector, as previously described. [11] When using biphasic catalysis,h omogeneous samples,o btained after intensivem ixing, were diluted in DMSO. Ther esulting concentrations thusr efer to the amount of product present in the total reaction volume.A ll calibrationc urves were prepared with authentic samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle these difficulties, many enzymatic processes have been developed using either glycoside hydrolases or phosphorylases or the mentioned GTs for the generation of various glucosides (Desmet et al, ). However, whereas glycoside hydrolases often suffer from an unfavorable equilibrium, typically shifted towards hydrolysis rather than the synthesis reaction, resulting in low yields (Desmet and Soetaert, ), glycoside phosphorylases require high concentrations of acceptor molecules for efficient catalysis (De Winter et al, ). The main constraint to the use of GTs in biocatalysis is the need for equimolar amounts of UDP‐glc, which is very expensive and rarely available in large quantities.…”
mentioning
confidence: 99%
“…It has been suggested that the main problem is the enzyme’s low affinity for such compounds, which cannot be compensated by increasing the acceptor concentrations because of their low solubility 7a,b. Although increased transglycosylation rates have been reported upon addition of organic solvents,7b,c saturation of the enzyme has never been achieved and productivity has generally remained too low for practical applications. With resveratrol, for example, the best result has been obtained in 20 % of the ionic liquid AMMOENG 101, but that only generated 3 m M of resveratrol 3‐α‐glucoside 7b.…”
Section: Methodsmentioning
confidence: 99%